The particle size distribution (PSD) as criteria for comparison of silver powders obtained by different methods of synthesis and by conditions of electrolysis - Avramović, Ljiljana; Bugarin, Mile; Milanović, Dragan; Conic, Vesna; Pavlović, Miroslav M.; Vukovic, Marina; Nikolic, Nebojsa D. (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
Production of silver powders via electrochemical and chemical routes has been considered. The galvanostatic and potentiostatic regimes of electrolysis from the nitrate and the ammonium electrolytes were used for electrolytic synthesis of Ag powders. Reduction with hydrazine was used for chemical synthesis. The synthesized Ag powders were examined by the scanning electron microscopic (SEM) and the particle size distribution (PSD) analysis of the obtained particles. The smallest particle sizes with the largest volume ratios (8.4–8.9 %) were obtained for powders produced from the ammonium electrolyte using the galvanostatic and the potentiostatic regimes of electrolysis at the current density or overpotential larger than the limiting diffusion current density, as well as for the chemically synthesized powder. The pine-like dendrites were obtained by the processes of electrolysis, while agglomerates of the grains were obtained by the chemical synthesis. In spite of strong difference at the macro level, the similarity at the micro level was observed among these particles. The both type of the particles consisted of approximately spherical grains. The obtained Ag powders were mutually compared in order to perceive advantages and lacks of their production via electrochemical and chemical routes.